ATTITUDE AND BEHAVIOR OF PEOPLE IN RELIGIOUS PLURALITY: Study of Social Reality About Interfaith Interaction in Tegalasri Village, Wlingi District, Blitar Regency - Mujadi, Mujadi; Susianto, Heri; Sholahuddin, Agus; Sadhana, Kridawati (IJRDO - Journal of Social Science and Humanities Research, 2018)
The purpose of the study is to describe and analyze the attitudes and behaviors of tolerance between religions, as well as efforts to create inter-religious harmony in the village of Tegalasri, Wlingi District, Blitar Regency. Data collection techniques using observation, in-depth interviews and documentation. The data analysis technique uses the qualitative data analysis model Strauss and Corbin consisting of an open coding stage, pivot coding, and selective coding. Results of the study: the interaction between religious believers is reflected in the behavior of each other to attend invitations to commemorate other religious holidays, to help build places of worship of other religions in groups, and to participate in celebrating other religious festivals. highway. Community relations are reflected in the work behavior of the worship places and the surrounding environment, attending the invitation of neighbors who have a duty, distributing qurban meat, maintaining order and tranquility when there are religious events. Efforts to create harmony between religious groups are carried out by: conducting deliberations in solving problems, social and humanitarian activities through home surgery programs, and youth empowerment through the Youth Organization program